Pengembangan Media Pembelajaran Yang Praktis dan Efektif Menggunakan Moodle Untuk Sekolah Menengah Kejuruan - Risdal Yosli; Hasan Maksum (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
The method of delivering learning by orally as well as giving a note in the form of copy or note, is less successful in time and is not maximally obtained by a student. The purpose of this research is to produce practical and effective learning media used by teacher and student at vocational high school. Web-based learning media using model 3.11.3+, which is applied to the domain and hosting. The type of this research is RD (research development), and the product development models are 4D; define, design, develop and disseminate. The instruments used are questionnaire, material, practically and English questions. The subjects of research are teacher and student of SMK Pratama Padang. Data analysis techniques are product validity testing, practical analysis technique and product effectiveness analysis technique. The levels of practicality of the product are 85 (teacher’s respondent) in the practical category and 81.99 (student’s respondent) in the very practical category. The level of product effectiveness based on the gain score reached 0.45, in the medium category.